2021
DOI: 10.26650/ibr.2021.51.0115
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sustainability Report, Financial Performance, and Ownership Structure: Research on The Turkish Banking Sector

Abstract: The financial statements of companies have been evaluated in financial performance analysis for many years. However, today, investors and business stakeholders, who want to invest in businesses, demand not only the information presented in financial statements, but also non-financial information to see future status and test whether it have a sustainable structure. In this context, the reporting of information on the economic, social, and environmental dimensions of businesses is possible through sustainabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
6
0
1
Order By: Relevance
“…Based on the findings of Xu and Wang [35], this study also uses the logged value of EBITDA. The financial performance measures used in the paper are quite often used by scholars in similar studies [4,[28][29][30][31][32][33] and are defined as accounting-based measures derived from accounting calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the findings of Xu and Wang [35], this study also uses the logged value of EBITDA. The financial performance measures used in the paper are quite often used by scholars in similar studies [4,[28][29][30][31][32][33] and are defined as accounting-based measures derived from accounting calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Do gan and Kevser [30], having studied the activities of 10 banks from the Turkish banking sector for 2013-2018, found that ESG indicators from their published sustainability reports do not affect their financial performance (ROA, ROE). Emir and Kıymık [31], after examining the role of GRI sustainability reports of BIST Metal Goods companies listed on the ISE for 2014-2018 in supporting their financial performance measures (ROA, ROE, ROC, profit before tax, growth rate in total assets), found a significant positive impact on the first four indicators and a significant negative impact on the growth rate in total assets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There was also a significant positive effect of leverage on ROA in the overall and subcategory models used, although no such effect was observed for the control variable size. Doğan and Kevser (2021) 2023) examined the impact of sustainability reports on financial performance measures (ROA and Tobin's Q) of 46 Turkish companies listed on the ISE for 2016-2020. They found a significant positive effect on ROA and its absence in relation to Tobin's Q.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the high level of recognition and a strong correlation with the NFRD and CSRD regulations, bank compliance with the GRI Standard is widely assessed in the literature; however, with scoring procedures using various methods (Smit and van Zyl 2016;Masud et al 2018;Do gan and Kevser 2021). Along with its general acceptance and the existence of bank-specific guidelines tailored for the thorough evaluation of members in the financial sector, the representation of scoring by GRI guidelines in the literature highly outnumbers that performed by the ACT and ISO guidelines.…”
Section: Relevant Literaturementioning
confidence: 99%